How are African governments tracking adaptation to climate change? Updates from work to collate and analyze adaptation indicators in NDCs and NAPs - Nowak, Andreea C.; Njunguna, Lucy (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Presentation to AGNES meeting, July 2022